PENGARUH MOTIVASI BELAJAR DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA SMK NURUL HUDA BAROS - Hudri, Muhamad; Atiah, Atiah; Febrianti, Ruli Eka; Sudiharto, Sudiharto (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of learning motivation on students learning outcomes at SMK Nurul Huda Baros. The background of this research is based on the phenomenon of declining student enthusiasm for learning amid increasing vocational education demands. In vocational education, learning motivation is an essential factor because it not only affects academic achievement but also determines student’s readiness for work. This research employed a quantitative associative approach with a population consisting of all students of SMK Nurul Huda Baros in the 2025/2026 academic year. A total of 30 students from grade XI were selected as samples using a purposive sampling technique. The independent variable (X) is learning motivation, while the dependent variable (Y) is students learning outcomes. Data were collected through a learning motivation questionnaire and documentation of students report card scores for the 2024/2025 academic year. Data analysis was conducted using simple linear regression to examine the relationship between the two variables. The results of the study indicate that learning motivation has a positive and significant effect on students learning outcomes, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.421. This means that 42.1% of the variation in students learning outcomes can be explained by learning motivation, while the remaining 57.9% is influenced by other factors such as teaching methods, school environment, and parental support. The study also found that intrinsic motivation such as curiosity, responsibility, and satisfaction in learning was more dominant in improving student achievement than extrinsic motivation such as praise and rewards. Based on these findings, teachers and schools are encouraged to enhance motivation programs through contextual learning activities, inspirational seminars, and supportive learning environments. This study is expected to serve as a reference for developing learning strategies in vocational schools to improve educational quality and students’ employability.